One-Year Clinical Outcome in End-Stage Heart Failure: Comparison of “High Urgent” Listing for Heart Transplantation with Mechanical Circulatory Support Implantation - Sunavsky, Jakub; Zittermann, Armin; Oezpeker, Cenk; Fujita, Buntaro; Fuchs, Uwe; Gummert, Jan F.; Schulz, Uwe (The Thoracic and Cardiovascular Surgeon, 2015)
Background Heart transplantation (HTx) is still considered the therapeutic gold standard in end-stage heart failure.Methods In “high urgent” (HU)-listed patients for HTx (n = 274) and patients receiving left ventricular assist device (LVAD) implants (n = 332), we compared 1-year overall survival (primary endpoint) and 1-year probability of HTx and therapy failure (the need for LVAD implantation in HU-listed patients or the need for HU listing in LVAD patients) (secondary endpoints).Results In the HU and LVAD group, 1-year survival was 86.8 and 64.7%, respectively (p < 0.001). The propensity score (PS)-adjusted hazard ratio of mortality did not differ between the groups and for the LVAD group (reference = HU group) was = 1.36 (95% confidence interval [CI]: 0.85–2.19; p = 0.198). The PS-adjusted hazard ratio for the failure to receive HTx for the LVAD group (reference = HU group) was = 9.77 (95% CI: 6.00–15.89; p < 0.001). The corresponding hazard ratio for therapy failure for the LVAD group was = 0.16, 95% CI: 0.10–0.27; p < 0.001).Conclusion Despite considerable differences in the probability of HTx and therapy failure, 1-year overall survival was similar in HU and LVAD patients.
Keywords: end-stage heart failure; heart transplantation; mechanical circulatory support; survival; mortality; high urgent listing